Harmoni Ekonomi Dan Kesehatan Sosialisasi Konsep Desa Konservasi Berbasis Tanaman Obat Keluarga (Toga) Di Ngasem, Karanganyar - Rastra Langlang Buana Rahmansyah; Ahmad Yasin Amanullah; Yunika Tussa’diyah; Erika Dzikri Masita; Santhyami (Jurnal Masyarakat Indonesia (Jumas), 2024)
The community service was conducted in Ngasem Village, Karanganyar, Central Java on July 6, 2024. The service was conducted by a team of students from the Student Organization Capacity Strengthening Program (PPK Ormawa) Biology Lotus (Biolotus), Biology Education, Faculty of Teacher Training and Education (FKIP) at Universitas Muhammdiyah Surakarta. The aim of this service is to familiarize individuals with the idea of conservation villages by use of the Family Medicinal Plants (TOGA) program. The activity techniques include of lectures, pre-posttests, and TOGA biodiversity identification. The participants demonstrated a strong comprehension of the Conservation Village idea, with a notable gain in knowledge of 18.06%. Additionally, the findings of the biodiversity mapping identification revealed that the community successfully planted 10 different varieties of TOGA on the designated site. Based on the identification results, there are a minimum of 9 significant TOGA kinds that have either failed to thrive or have not been cultivated. This community service activity not only offers tangible advantages to the community, but also has the potential to make significant scientific contributions to the campus environment, particularly by providing valuable experience for Ormawa to enhance its organizational capacity.